2014
DOI: 10.1209/0295-5075/106/16001
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of native defects in SnO under strain

Abstract: Tin monoxide (SnO) has promising properties to be applied as a p-type semiconductor in transparent electronics. To this end, it is necessary to understand the behavior of defects in order to control them. We use density functional theory to study native defects of SnO under tensile and compressive strain. We show that Sn vacancies are more stable under tension and less stable under compression, irrespectively of the charge state. In contrast, O vacancies behave differently for different charge. It turns out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
(48 reference statements)
2
11
0
Order By: Relevance
“…It is found that both bulk and ML SnO are indirect band gap semiconductor, in which VBM is situated among Γ-M line. However, the CBM is located at M point for bulk and shifted to Γ point for ML which is in excellent agreement with previous theoretical reports 13 14 15 . The involvement of spin-orbital coupling (SOC) is found to have no effect on the band structure, i.e.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…It is found that both bulk and ML SnO are indirect band gap semiconductor, in which VBM is situated among Γ-M line. However, the CBM is located at M point for bulk and shifted to Γ point for ML which is in excellent agreement with previous theoretical reports 13 14 15 . The involvement of spin-orbital coupling (SOC) is found to have no effect on the band structure, i.e.…”
Section: Resultssupporting
confidence: 92%
“…and X a chalcogen atom, such S, Se, or Te) 9 10 11 and black phosphorus 12 (BP) that were recently extensively studied. More recently, layered tin (II) oxide (SnO) was found to show excellent semiconducting performances in which bipolar conductivity can be easily realized 13 14 15 16 . It is a rare example of layered oxide semiconductors that holds promise for a wide variety of technological applications 14 17 18 , which makes it quickly become the subject of significant theoretical and experimental investigations 1 13 14 18 19 .…”
mentioning
confidence: 99%
See 3 more Smart Citations